THE CORRELATION BETWEEN STUDENTS’ ANXIETY AND SPEAKING PERFORMANCE IN ENGLISH CLASSES AT SMA NEGERI 1 KRADENAN - Tiara Nurwanti; Endang Susilowati; Eka Fanti Sulistiyaningsih (Journalistics: Journal of English Teaching and Applied Linguistics, 2025)
Anxiety significantly impacts students' language learning processes, particularly influencing their ability to perform effectively in speaking activities. This study aims to determine the correlation between students' anxiety and their speaking performance at SMA Negeri 1 Kradenan, involving a sample of 72 eleventh-grade students. A quantitative approach was employed, utilizing Pearson correlation analysis to assess the data. The Foreign Language Speaking Anxiety Scale questionnaire, adapted from Horwitz et al. (1995), was used to measure anxiety levels, while speaking performance scores were collected from teachers as secondary data. The results showed a statistically significant negative correlation (r = -0.926, p < 0.05). These findings indicate a strong negative correlation, suggesting that higher anxiety levels are associated with lower speaking performance. To address these challenges, educators must create a supportive learning environment that fosters student confidence. Based on the study's findings, it is recommended that educators implement effective strategies to reduce anxiety, such as relaxation techniques and small group speaking practices. These approaches can help improve students' confidence and enhance their speaking performance, leading to a more positive language learning experience. By addressing anxiety, educators can significantly enhance students' engagement and success in language learning.